Composite thermal fluid downhole corrosion test device and test method

By designing a composite thermal fluid downhole corrosion test device, the device includes a thermal insulation bushing, a test piece stop ring, a test piece base and a test piece fixing ring, the problem of difficulty in realizing and effective detection of downhole corrosion in the prior art is solved, and efficient and safe oil well production and corrosion prevention processes are achieved.

CN115977612BActive Publication Date: 2025-04-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202111204815.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-15
Publication Date
2025-04-11
Estimated Expiration
2041-10-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively detect corrosion conditions and corrosion rates under composite thermal fluid wells, and conventional devices are complex in structure and materials are not heat-insulated, which can easily lead to thermal dew point loss and affect the normal injection and production of oil wells.

Method used

A composite thermal fluid downhole corrosion testing device is designed. The device includes a thermal insulation bushing, a test piece stop ring, a test piece base and a test piece fixing ring. It can be placed in any position in the pipe column, and is easy to install and operate. It does not touch the pipe wall, nor will it fall into the bottom of the well. It is also resistant to high temperature and high pressure and corrosion.

Benefits of technology

It realizes the real and effective detection of corrosion conditions and corrosion rates underground, avoids thermal dew point losses, ensures normal injection and production of oil wells, and provides a basis for the formulation of targeted anti-corrosion processes on site.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115977612B_ABST
    Figure CN115977612B_ABST
Patent Text Reader

Abstract

The present invention provides a composite thermal fluid downhole corrosion test device and a test method. The composite thermal fluid downhole corrosion test device comprises a thermal insulation bushing, a test piece retaining ring, a test piece base and a test piece fixing ring. The thermal insulation bushing comprises a bushing and a steel liner. The bushing is sleeved at the outer middle position of the steel liner. The test piece retaining ring is welded to the inner bottom end of the steel liner. The test piece base is clamped on the upper part of the test piece retaining ring. Three test piece grooves are provided on the test piece base. Test pieces of three different materials are respectively placed in the three test piece grooves. The three test pieces are fixed by the test piece fixing ring at the upper end of the steel liner. The composite thermal fluid downhole corrosion test device and the test method can be placed at any position in the pipe column, and the installation and operation are convenient. It does not touch the pipe wall and will not fall into the bottom of the well. At the same time, it is resistant to high temperature and high pressure and corrosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heavy oil production, and in particular to a composite thermal fluid downhole corrosion testing device and a testing method. Background Art

[0002] my country is rich in heavy oil resources, with proven reserves of about 4 billion tons, accounting for more than 20% of oil reserves, and is becoming the main force in increasing reserves and production of my country's oil resources. Due to its high viscosity, heavy oil has great flow resistance in the formation. Steam injection is the main way to develop heavy oil reservoirs. Steam injection boilers are required to produce and supply a large amount of steam. In the process of generating steam, steam injection boilers will also produce a large amount of flue gas. For example, the annual flue gas generation of Shengli Oilfield reaches nearly 8 billion Nm 3 , usually invalid emissions are taken after meeting the standards.

[0003] Flue gas is the gas produced from the flue or chimney when carbon-containing fuel is burned. It usually contains 75% nitrogen, 15% carbon dioxide, 5% water, 3% oxygen and other nitrogen oxides. Carbon dioxide and nitrogen in flue gas can effectively reduce crude oil viscosity and replenish formation energy. The composite thermal fluid of flue gas and steam injected into the oil layer can effectively improve the development effect of heavy oil thermal recovery. However, during the field test, it was found that the acidic corrosive gases such as CO2, nitrogen oxides, and residual O2 in the flue gas injected into the well, under the high temperature and high pressure environment of saturated wet steam or hot water, aggravated the corrosion of steel steam injection insulation oil pipes, casings or screens and other pipes and downhole tools. In order to reduce the corrosion of composite thermal fluid on downhole pipes and tools, it is necessary to first evaluate the corrosion effect of the injected fluid medium on the downhole material, so as to take targeted anti-corrosion process measures to reduce the corrosion effect.

[0004] The injection of corrosion inhibitors has the characteristics of low cost, quick effect and simple operation. It is one of the most commonly used protective measures in oil and gas wells. In order to reduce the corrosion of composite thermal fluids on downhole pipes and tools, chemical corrosion inhibitors are often added to reduce the impact of corrosion. Due to the variability and complexity of corrosion, the quality of corrosion inhibitors is not only affected by its own molecular structure, type of corrosive medium, type of metal itself, environment and compatibility, but also by some other parameters in the production process, such as pressure, temperature, multiphase, flow rate, components and other factors. At present, the evaluation methods used for corrosion inhibitors mainly include static evaluation method, dynamic evaluation method (rotating hanging plate method), electrochemical method, etc. These methods cannot simulate the on-site corrosion environment well, and the evaluation process of corrosion inhibitors should be carried out in an environment equivalent to on-site conditions as much as possible.

[0005] The utility model patent 201320731476.3 invented by Xu Xiaofeng et al. provides a downhole corrosion hanging plate test device, which includes a bailing head, a downhole choke, and a corrosion hanging plate seat, wherein the bailing head is arranged at the top of the downhole choke, the corrosion hanging plate seat is fixedly arranged at the bottom of the downhole choke, and the side wall of the downhole choke is provided with slips. When the test device is in use, after the downhole choke is connected with the corrosion hanging plate seat, the whole device is lowered to the designed depth by steel wire, and then the slips are lifted up to fix the slips on the inner wall of the oil pipe to realize the in-situ monitoring of the corrosion condition of the downhole oil pipe. The above test device is anchored by slips. On the one hand, due to the high hardness of the slips, it may cause certain damage to the inner wall of the oil pipe during its operation; on the other hand, due to the choke connected above the corrosion hanging plate seat, the structure is relatively complex, and the disturbance to the fluid is relatively large, which leads to the distortion of the monitoring data and cannot objectively and truly reflect the corrosion condition of the downhole oil pipe.

[0006] Patent 201610371105.7 invented by Li Bowen et al. provides a method and device for downhole stress corrosion testing. The device has a stress corrosion testing unit, a protective shell and a connecting joint, wherein the stress corrosion testing unit is a group of multiple groups installed in the cavity of the protective shell, one end of the connecting joint is installed on the thread at the tail end of the protective shell, and the corrosion testing unit group installed in the hollow cavity of the protective shell is pressed, and the other end of the connecting joint is connected to the downhole device to realize stress corrosion testing in the downhole environment. The device has a complex structure and the internal and external materials are not heat-insulated. If it is used in a composite thermal fluid, it is easy to cause thermal dew point loss between the insulated oil pipes, affecting the normal injection and production of the oil well.

[0007] The Chinese application with application number: CN201210222014.9 discloses a high temperature and high pressure constant load stress corrosion test method and device, which realizes the constant load stress corrosion test of metal materials under a certain stress state and in the action of high temperature and high pressure gas phase or liquid phase corrosive medium, but it cannot simulate the influence of multiphase flow erosion in the working environment.

[0008] The Chinese application with application number: CN201510296362.4 discloses a stress corrosion test device that simulates metal materials under actual working conditions, and simulates the influence of medium on material scouring by rotating the test piece inside the device. However, this method is a laboratory simulation method after all, which is out of the actual working conditions of high temperature, high pressure, and multiphase flow scouring in the well, and there is a gap between the test results and the actual situation.

[0009] The patent invented by Sun Liang et al.: 201911416333.1, discloses a corrosion inhibitor performance evaluation device and a corrosion inhibitor performance evaluation method. The evaluation device includes a raw material tank for containing corrosive media, an evaluation tank for containing evaluation samples, and a metering pump for circulating corrosive media. It can simulate the flow environment of the pipeline system, thereby simulating the on-site corrosion environment, and screening out the best corrosion inhibitor and its concentration that meet the working conditions. However, the simulated test environment still cannot achieve the performance evaluation of corrosion inhibitors under real complex on-site working conditions.

[0010] Patent 201910040205.5 invented by Nie Junbo et al. discloses an integrated corrosion inhibitor evaluation device and its use method, which combines the bottle body with the automatic temperature control and stirring system, and designs an integrated structure of the outer cover, inner cover and bracket, which effectively solves the problem of difficulty in laboratory corrosion inhibitor evaluation. However, it still belongs to the scope of laboratory evaluation and cannot realize the performance evaluation of corrosion inhibitors under real complex field conditions.

[0011] The patent 201611224268.9 invented by Wang Yun et al. discloses a method for evaluating the corrosion inhibition efficiency of corrosion inhibitors. It uses a jet corrosion inhibitor evaluation system to carry out multiple sets of corrosion inhibitor evaluation experiments, which can simulate corrosion conditions under different well depths, different pressures, different temperatures, and different gas flow rates. However, this method is a laboratory simulation method after all, and there is a gap between the test results and the actual situation on site.

[0012] The above existing technologies are greatly different from the present invention and fail to solve the technical problems we want to solve. For this reason, we have invented a new composite thermal fluid downhole corrosion testing device and test method. Summary of the invention

[0013] The purpose of the present invention is to provide a composite thermal fluid downhole corrosion testing device and test method which does not touch the pipe wall and does not fall into the bottom of the well and is resistant to high temperature, high pressure and corrosion.

[0014] The purpose of the present invention can be achieved through the following technical measures: a composite thermal fluid downhole corrosion testing device, which includes a thermal insulation bushing, a test piece retaining ring, a test piece base and a test piece fixing ring. The thermal insulation bushing includes a bushing and a steel liner. The bushing is sleeved on the outer middle position of the steel liner, the test piece retaining ring is welded to the bottom end of the inner part of the steel liner, the test piece base is clamped on the upper part of the test piece retaining ring, and three test piece grooves are provided on the test piece base. Test pieces of three different materials are respectively placed in the three test piece grooves, and the three test pieces are fixed at the upper end of the steel liner by the test piece fixing ring.

[0015] The purpose of the present invention can also be achieved by the following technical measures:

[0016] The test piece retaining ring and the steel liner are made of steel material, and the bushing, the test piece base and the test piece fixing ring are made of high temperature resistant and corrosion resistant sealing insulating materials.

[0017] The three test piece grooves are spaced 120 degrees apart.

[0018] The test piece fixing ring is provided with three rectangular fixing holes with the same cross-sectional area as the test piece and spaced 120 degrees apart.

[0019] The composite thermal fluid downhole corrosion testing device is placed in a coupling between two adjacent steam injection pipe strings.

[0020] The object of the present invention can also be achieved by the following technical measures: a composite thermal fluid downhole corrosion test method, the composite thermal fluid downhole corrosion test method comprising:

[0021] Step 1: Pull out the original well production string;

[0022] Step 2, lowering the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion testing device;

[0023] Step 3, starting the steam composite thermal fluid injection process;

[0024] Step 4, stewing well;

[0025] Step 5, spray;

[0026] Step 6: Pull out the underground heat-insulated oil pipe and the corrosion testing device, and take out the corrosion coupon;

[0027] Step 7: After the corrosion coupon is decontaminated, it is further degreased and dehydrated to obtain the weight loss of the coupon and calculate the corrosion rate.

[0028] The composite thermal fluid downhole corrosion testing device includes a thermal insulation sleeve, a test piece retaining ring, a test piece base and a test piece fixing ring. The thermal insulation sleeve includes a sleeve and a steel liner. The sleeve is sleeved on the outer middle position of the steel liner. The test piece retaining ring is welded to the inner bottom end of the steel liner. The test piece base is clamped on the upper part of the test piece retaining ring. Three test piece grooves are provided on the test piece base. Test pieces of three different materials are respectively placed in the three test piece grooves. The three test pieces are fixed at the upper end of the steel liner by the test piece fixing ring. The composite thermal fluid downhole corrosion testing device is installed in a coupling between two adjacent steam injection pipe columns.

[0029] The purpose of the present invention can also be achieved by the following technical measures:

[0030] In step 2, while lowering the insulated oil pipe, the corrosion testing device is also lowered; the steam injection insulated oil pipe is a high vacuum or aerogel insulated oil pipe.

[0031] In step 3, steam and composite thermal fluid are injected, and the composite thermal fluid is continuously injected from the insulated oil pipe, and the designed amount of composite thermal fluid is injected according to the requirements of the reservoir.

[0032] In step 4, after the injection of the composite thermal fluid is completed, a temperature-resistant pressure gauge is installed at the wellhead and the well is shut down. The shut down time depends on the injection volume of the composite thermal fluid and the wellhead pressure, and should be adjusted according to actual conditions.

[0033] In step 5, the spraying is controlled by an oil nozzle to prevent the formation from being disturbed and the sand filter pipe from being eroded due to excessive spraying speed. When the liquid volume reaches 3t / d, the pumping is switched to suction.

[0034] The composite thermal fluid downhole corrosion testing method further includes, after step 6, observing and recording the surface corrosion state and corrosion product adhesion of the hanging piece, cleaning it with clean water, and wiping it dry with filter paper.

[0035] In step 7, the corrosion coupon is placed in a container of petroleum ether or acetone, and the oil on the surface of the corrosion coupon is removed with absorbent cotton, and then immersed in sewage ethanol for 5 minutes for further degreasing and dehydration; then the corrosion coupon is placed in the prepared pickling solution and immersed for 5 minutes, and at the same time, a small amount of absorbent cotton is clamped with tweezers to gently wipe the corrosion products on the surface of the coupon; the coupon is taken out from the cleaning solution, and the residual acid on the surface is washed off with tap water, and then the coupon is immediately immersed in a sodium hydroxide solution, rinsed with tap water after 30 seconds, and then immersed in anhydrous ethanol for 5 minutes, and washed and dehydrated twice; the coupon is taken out and placed on filter paper, blown dry with cold wind, and then wrapped with filter paper, placed in a dryer, and weighed after 24 hours to obtain the weight loss of the coupon, and the corrosion rate is calculated.

[0036] In step 7, the corrosion rate is calculated as:

[0037]

[0038] Where: r c represents the average corrosion rate in millimeters per year; m represents the mass of the test piece before the test in grams; m1 represents the mass of the test piece after the test in grams; S represents the total area of ​​the test piece in square centimeters; t represents the test time in hours; ρ represents the density of the test piece material in grams per cubic centimeter.

[0039] The composite thermal fluid downhole corrosion testing method also includes, after step 7, repeating steps 1 to 6, during the injection of the composite thermal fluid in step 3, the pump truck is connected to the oil pipe gate through a hose, and the corrosion inhibitor solution is continuously or segmentally injected, and the corrosion inhibition efficiency of the corrosion inhibitor under different field conditions is evaluated by the weight loss method.

[0040] The composite thermal fluid downhole corrosion test device and test method of the present invention can be placed at any position in the pipe string, is easy to install and operate, does not touch the pipe wall, and will not fall into the bottom of the well. It is resistant to high temperature and high pressure and corrosion. Compared with the prior art, it has the following advantages and beneficial effects:

[0041] (1) The device of the present invention is fixed in the couplings of two adjacent steam injection insulation pipe columns, and can be used as a conventional insulation bushing to avoid the dew point heat loss of steam and not affect the normal injection of composite thermal fluid. At the same time, it can detect the actual corrosion situation and corrosion rate in the well.

[0042] (2) The device of the present invention can be lowered into any position of the wellbore along with the steam injection insulation pipe string, and can fully contact with the composite thermal fluid in the pipe string to truly and effectively detect the corrosion condition of the position downhole. The corrosion hanging piece will neither touch the pipe wall nor fall into the bottom of the well. The device material is resistant to high temperature and corrosion, and the device structure is simple, and it is easy to install and disassemble.

[0043] (3) The device and method of the present invention can measure the corrosion rate of composite thermal fluid on different materials in the well, at different locations in the well, at different throughput cycles, and at different oxygen contents, different carbon dioxide contents, and different temperatures of the composite thermal fluid. It can accurately reflect the corrosion influencing factors and the degree of corrosion influence during the downhole test, and provide a basis for formulating targeted anti-corrosion processes on site.

[0044] (4) The method for evaluating the performance of corrosion inhibitors provided by the present invention can be used on-site to conduct corrosion tests under different well depths, different temperatures, different gas flow rates, and different corrosion inhibitor injection methods, effectively evaluate the corrosion inhibition efficiency of the corrosion inhibitor, and determine the corrosion inhibitor injection rate. The field test of corrosion inhibitor evaluation is more reliable, and provides field test data for the development of new corrosion inhibitors and the design of efficient anti-corrosion processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a cross-sectional view of a downhole corrosion test hanging device in a specific embodiment of the present invention;

[0046] Figure 2 It is a top view of a downhole corrosion test hanging device in a specific embodiment of the present invention;

[0047] Figure 3 It is a plan view of three underground corrosion test coupons made of different materials in a specific embodiment of the present invention;

[0048] Figure 4 It is a flow chart of a specific embodiment of the composite thermal fluid downhole corrosion testing method of the present invention;

[0049] Figure 5 It is a schematic diagram of the corrosion rate of the test coupons of different downhole materials by the composite thermal fluid in a specific embodiment of the present invention;

[0050] Figure 6 It is a schematic diagram of the corrosion rate of the test coupons at different downhole depths by the composite thermal fluid in a specific embodiment of the present invention;

[0051] Figure 7 It is a schematic diagram of the corrosion rate of the test coupons with different throughput cycles by the composite thermal fluid in a specific embodiment of the present invention;

[0052] Figure 8 It is a schematic diagram of the corrosion rate of the test coupons with different oxygen contents in the composite thermal fluid in a specific embodiment of the present invention;

[0053] Fig. 9 It is a schematic diagram of the corrosion rate of test coupons with different carbon dioxide contents in a composite thermal fluid in a specific embodiment of the present invention;

[0054] Fig.10 It is a schematic diagram of the corrosion rate of the test coupons of the composite thermal fluid at different temperatures in a specific embodiment of the present invention;

[0055] Fig.11 It is a schematic diagram of evaluating the performance of the composite thermal fluid on the corrosion inhibitor at different downhole depths in a specific embodiment of the present invention;

[0056] In the figure: 1-test piece, 2-steel lining, 3-bushing, 4-test piece retaining ring, 5-test piece base, 6-test piece fixing ring, 7-test piece groove. DETAILED DESCRIPTION

[0057] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0058] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.

[0059] like Figure 1 As shown, the composite thermal fluid downhole corrosion testing device of the present invention is an improvement on the structure of the thermal insulation liner of the current thermal recovery well. The thermal insulation liner includes a steel liner 2 and a liner 3, wherein the liner 3 is generally made of graphite or polytetrafluoroethylene material, and can also be other thermal insulation materials.

[0060] The bushing 3 is placed in the middle of the outer part of the steel liner 2, and the length of the steel liner 2 on both sides is 12mm longer than the bushing 3. The test piece retaining ring 4 is welded to the bottom end of the inner part of the steel liner 2, and the bottom surface of the retaining ring is flush with the lower end of the steel liner 2. The material of the test piece retaining ring 4 is the same as that of the steel liner 2. The test piece base 5 is clamped on the test piece retaining ring 4, and the cross-section of the test piece base 5 is the same as the top surface of the test piece retaining ring 4. Three test piece grooves 7 are provided on the test piece base 5, and the positions are shown in the attached figure. Figure 2 The three test piece grooves are spaced 120° apart. The test piece 1 is placed in the test piece groove 7. The three test pieces are made of three materials for evaluating corrosion. To distinguish the three different materials, the test pieces are placed in the test piece groove 7. Figure 3 A hole is punched at one end of the test piece as a mark. The test piece fixing ring 6 has three rectangular fixing holes with the same cross-sectional area as the test piece, and the interval is also 120°. The test piece fixing ring 6 is vertically passed through by the three test pieces and is sealed on the straight section at the upper end of the steel liner 2 to fix the test piece 1. The test piece base 5 and the test piece fixing ring 6 can be made of polytetrafluoroethylene material, or other high temperature resistant and corrosion resistant sealing insulating materials.

[0061] The thermal insulation bushing is a commonly used supporting tool for steam injection in thermal recovery wells. It is placed in the coupling between two adjacent steam injection pipe strings to eliminate the heat dissipation at the pipe string connection. The device of the present invention is designed on the thermal insulation bushing and can be lowered into any position underground as needed. Even multiple test pieces can be lowered into one well to simultaneously detect the corrosion degree at different depths.

[0062] like Figure 4 As shown, Figure 4 The present invention is a flowchart of a specific embodiment of the composite thermal fluid downhole corrosion testing method of the present invention.

[0063] Step 101, pulling out the original well production string;

[0064] Step 102: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device. While lowering the insulation oil pipe, lower the corrosion test device;

[0065] The steam injection insulated oil pipe is a high vacuum or aerogel insulated oil pipe, which reduces the heat loss of the wellbore;

[0066] The thermal insulation bushing is generally made of graphite or polytetrafluoroethylene, or other thermal insulation materials;

[0067] Step 103, start the steam composite thermal fluid injection process, start to inject steam and composite thermal fluid, the composite thermal fluid is continuously injected from the insulated oil pipe, and the designed amount of composite thermal fluid is injected according to the requirements of the oil reservoir;

[0068] Step 104, well soaking. After the injection of the composite thermal fluid is completed, a temperature-resistant pressure gauge is installed at the wellhead and well soaking begins. The well soaking time depends on the injection volume of the composite thermal fluid and the wellhead pressure. The well soaking time should be adjusted according to the actual situation. Generally, the well soaking time is 3 to 5 days.

[0069] Step 105, spraying. Use an oil nozzle to control the spraying to prevent the formation from being disturbed and the sand filter tube from being eroded due to excessive spraying speed. When the spraying reaches 3t / d of liquid, switch to pumping;

[0070] Step 106, pull out the underground heat-insulated oil pipe and the corrosion testing device, and take out the corrosion coupon;

[0071] Step 107, observe and record the surface corrosion state and corrosion product adhesion of the coupon, clean it with clean water, and wipe it dry with filter paper;

[0072] Step 108, place the corrosion coupon in a container of petroleum ether or acetone, remove the oil stains on the surface of the corrosion coupon with absorbent cotton, and then soak it in sewage ethanol for 5 minutes for further degreasing and dehydration. Then soak the corrosion coupon in the prepared pickling solution for 5 minutes, and use tweezers to hold a small amount of absorbent cotton to gently wipe the corrosion products on the surface of the test piece. Take out the test piece from the cleaning solution, rinse the surface residual acid with tap water, and immediately immerse the test piece in sodium hydroxide solution. After 30 seconds, rinse with tap water, and then soak it in anhydrous ethanol for 5 minutes, and wash and dehydrate twice. Take out the test piece and place it on filter paper, blow dry with cold air, then wrap the test piece with filter paper, place it in a dryer, and weigh it after 24 hours to obtain the weight loss of the coupon and calculate the corrosion rate. The corrosion rate calculation method is shown in Formula 1.

[0073]

[0074] Where: r c represents the average corrosion rate in millimeters per year (mm / a); m represents the mass of the test piece before the test in grams (g); m1 represents the mass of the test piece after the test in grams (g); S represents the total area of ​​the test piece in square centimeters (cm 2 ); t is the test time, in hours (h); ρ is the density of the test piece material, in grams per cubic centimeter (g / cm 3 ).

[0075] The following are several specific embodiments of corrosion rate experiments using the composite thermal fluid downhole corrosion testing device of the present invention.

[0076] Embodiment 1:

[0077] An experimental method for the corrosion rate of a composite thermal fluid on a hanging piece of different downhole materials comprises the following steps:

[0078] Step 1: Pull out the production string from the original well;

[0079] Step 2: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device, and at 800m downhole, lower the insulation oil pipe and the corrosion test device at the same time. The device is equipped with three materials commonly used in oil fields, namely new J55, N80, and P110;

[0080] Step 3, injecting composite thermal fluid into the well through the insulated oil pipe from the wellhead;

[0081] Step 4: stew the well;

[0082] Step 5: Spray;

[0083] Step 6: Pull out the underground heat-insulated oil pipe and the corrosion testing device, and take out the corrosion coupon;

[0084] Step 7: Observe the corrosion morphology of the corrosion coupon;

[0085] Step 8: Arrange the data: Arrange the weight loss of different downhole material corrosion hanging pieces, calculate the corrosion rate, and you can get the corrosion rate of different downhole materials, see Figure 5 .

[0086] from Figure 5 It can be seen that the corrosion rate of J55 steel grade hanging piece is 0.784mm / a, the corrosion rate of N80 steel grade hanging piece is 0.526mm / a, and the corrosion rate of P110 steel grade hanging piece is 0.485mm / a. The corrosion rates are all higher than the national industry standard of 0.076mm / a, and the impact on the material is: J55>N80>P110, and anti-corrosion process measures are required.

[0087] Embodiment 2:

[0088] An experimental method for the corrosion rate of a composite thermal fluid on a hanging piece at different downhole depths comprises the following steps:

[0089] Step 1: Pull out the production string from the original well;

[0090] Step 2: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device, and lower the insulation oil pipe and the corrosion test device at 10m, 100m, 300m, 500m, 800m, 1000m and 1200m downhole. The device is equipped with three materials commonly used in oil fields, namely J55, N80 and P110;

[0091] Step 3, injecting composite thermal fluid into the well through the insulated oil pipe from the wellhead;

[0092] Step 4: stew the well;

[0093] Step 5: Spray;

[0094] Step 6: Pull out the underground heat-insulated oil pipe and the corrosion testing device, and take out the corrosion coupon;

[0095] Step 7: Arrange the data: Arrange the weight loss of the corrosion hanging pieces at different downhole depths, calculate the corrosion rate, and you can get the corrosion rate at different downhole depths. Figure 6 .

[0096] from Figure 6 It can be seen that the higher the depth of the well, the higher the corrosion rate, which is higher than the national industry standard of 0.076mm / a, and the impact on the material is: J55>N80>P110.

[0097] Embodiment 3:

[0098] A method for testing the corrosion rate of a composite thermal fluid on a coupon with different throughput cycles comprises the following steps:

[0099] Step 1: Pull out the production string from the original well;

[0100] Step 2: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device. At 800m downhole, lower the insulation oil pipe and the corrosion test device at the same time. The device is equipped with three materials commonly used in oil fields, namely new J55, N80 and P110.

[0101] Step 3, injecting composite thermal fluid into the well through the insulated oil pipe from the wellhead;

[0102] Step 4: stew the well;

[0103] Step 5: Spray;

[0104] Step 6: Pull out the underground insulation oil pipe and corrosion test device, and take out the corrosion coupon;

[0105] Step 7: Arrange data: Arrange the weight loss mass of the coupons in the first throughput round, calculate the corrosion rate, and obtain the corrosion rate of the coupons in the first throughput round;

[0106] Step 8, repeating steps 1 to 7, using the coupons from the previous throughput round, and calculating the corrosion rate of the coupons from the second throughput round;

[0107] Step 9, repeating steps 1 to 7, using the coupons from the previous throughput round, and calculating the corrosion rate of the coupons from the third throughput round;

[0108] Step 10, repeating steps 1 to 7, using the coupons from the previous throughput round, and calculating the corrosion rate of the coupons from the fourth throughput round;

[0109] Step 11, repeating steps 1 to 7, using the coupons from the previous throughput round, and calculating the corrosion rate of the coupons from the fifth throughput round;

[0110] Step 12: Arrange data: Arrange the weight loss mass of the hanging pieces at different throughput cycles, calculate the corrosion rate, and you can get the corrosion rate of the hanging pieces at different throughput cycles, see Figure 7 ;

[0111] from Figure 7 It can be seen that as the throughput rounds increase, the corrosion rate tends to increase slowly, and the corrosion rate is higher than the national industry standard of 0.076mm / a, and the impact on the material is: J55>N80>P110.

[0112] Embodiment 4:

[0113] A method for testing the corrosion rate of coupons with different oxygen contents in a composite hot fluid comprises the following steps:

[0114] Step 1: Pull out the production string from the original well;

[0115] Step 2: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device. At 800m downhole, lower the insulation oil pipe and the corrosion test device at the same time. The device is equipped with three materials commonly used in oil fields, namely new J55, N80 and P110.

[0116] Step 3: injecting composite thermal fluid from the wellhead into the well through the insulated oil pipe, wherein the oxygen content in the composite thermal fluid is 5%;

[0117] Step 4: stew the well;

[0118] Step 5: Spray;

[0119] Step 6: Pull out the underground insulated oil pipe and the corrosion test device, take out the corrosion coupon, and calculate the corrosion rate when the oxygen concentration is 5%;

[0120] Step 7: Repeat steps 1 to 6. In step 3, the oxygen content in the composite hot fluid is 3%. Calculate the corrosion rate when the oxygen concentration is 3%.

[0121] Step 8: Repeat steps 1 to 6. In step 3, the oxygen content in the composite thermal fluid is 1%, and calculate the corrosion rate when the oxygen concentration is 1%.

[0122] Step 9, repeating steps 1 to 6, wherein the oxygen content in the composite thermal fluid in step 3 is 0.5%, and calculating the corrosion rate when the oxygen concentration is 0.5%;

[0123] Step 10: Arrange the data: Arrange the weight loss of the coupons with different oxygen contents, calculate the corrosion rate, and you can get the corrosion rate of the coupons with different oxygen contents, see Figure 8 ;

[0124] from Figure 8 It can be seen that: with the increase of oxygen concentration, the corrosion rate increases rapidly. The oxygen content is an important influencing factor causing the corrosion of the composite thermal fluid on the downhole pipe and tools. The corrosion rate is higher than the national industry standard of 0.076mm / a, and the impact on the material is: J55>N80>P110.

[0125] Embodiment 5:

[0126] A method for testing the corrosion rate of coupons with different carbon dioxide contents in a composite thermal fluid comprises the following steps:

[0127] Step 1: Pull out the production string from the original well;

[0128] Step 2: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device. At 800m downhole, lower the insulation oil pipe and the corrosion test device at the same time. The device is equipped with three materials commonly used in oil fields, namely new J55, N80 and P110.

[0129] Step 3: injecting composite thermal fluid into the well through the insulated oil pipe from the wellhead, wherein the carbon dioxide content in the composite thermal fluid is 25%;

[0130] Step 4: stew the well;

[0131] Step 5: Spray;

[0132] Step 6: Pull out the underground insulated oil pipe and the corrosion test device, take out the corrosion coupon, and calculate the corrosion rate when the carbon dioxide content is 25%;

[0133] Step 7, repeating steps 1 to 6, wherein the content of carbon dioxide in the composite thermal fluid in step 3 is 20%, and calculating the corrosion rate when the content of carbon dioxide is 20%;

[0134] Step 8, repeating steps 1 to 6, wherein the content of carbon dioxide in the composite thermal fluid in step 3 is 15%, and calculating the corrosion rate when the content of carbon dioxide is 15%;

[0135] Step 8, repeating steps 1 to 6, in step 3, the carbon dioxide content in the composite thermal fluid is 10%, and calculating the corrosion rate when the carbon dioxide content is 10%;

[0136] Step 9: Arrange the data: Arrange the weight loss of the coupons with different carbon dioxide contents, calculate the corrosion rate, and you can get the corrosion rate of the coupons with different carbon dioxide contents, see Fig. 9 ;

[0137] from Fig. 9 It can be seen that: with the increase of carbon dioxide concentration, the corrosion rate also increases rapidly. The carbon dioxide content is another important factor causing the corrosion of composite thermal fluid on downhole pipes and tools. The corrosion rate is higher than the national industry standard of 0.076mm / a, and the impact on the material is: J55>N80>P110.

[0138] Embodiment 6:

[0139] A method for testing the corrosion rate of coupons at different temperatures of a composite thermal fluid comprises the following steps:

[0140] Step 1: Pull out the production string from the original well;

[0141] Step 2: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device. At 800m downhole, lower the insulation oil pipe and the corrosion test device at the same time. The device is equipped with three materials commonly used in oil fields, namely new J55, N80 and P110.

[0142] Step 3: injecting composite thermal fluid into the well through the insulated oil pipe from the wellhead, and the wellhead injection temperature of the composite thermal fluid is 350° C.;

[0143] Step 4: stew the well;

[0144] Step 5: Spray;

[0145] Step 6: Pull out the underground insulated oil pipe and the corrosion test device, take out the corrosion coupon, and calculate the corrosion rate at an injection temperature of 350°C;

[0146] Step 7, repeating steps 1 to 6, wherein the injection temperature of the composite thermal fluid in step 3 is 300° C., and calculating the corrosion rate when the injection temperature is 300° C.;

[0147] Step 8, repeating steps 1 to 6, wherein the injection temperature of the composite thermal fluid in step 3 is 280° C., and calculating the corrosion rate when the injection temperature is 280° C.;

[0148] Step 9, repeating steps 1 to 6, wherein the injection temperature of the composite thermal fluid in step 3 is 250° C., and calculating the corrosion rate when the injection temperature is 250° C.;

[0149] Step 10: Arrange data: Arrange the weight loss mass of the coupons with different composite thermal fluid temperatures, calculate the corrosion rate, and you can get the corrosion rate of the coupons with different composite thermal fluid temperatures, see Fig.10 ;

[0150] from Fig.10It can be seen that: with the increase of the temperature of the composite hot fluid, the corrosion rate also increases, but the increase is relatively slow. The corrosion rate is higher than the national industry standard of 0.076mm / a, and the impact on the material is: J55>N80>P110.

[0151] Embodiment 7:

[0152] A test method for evaluating the performance of a corrosion inhibitor at different downhole depths using a composite thermal fluid comprises the following steps:

[0153] Step 1: Pull out the production string from the original well;

[0154] Step 2: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device, and lower the insulation oil pipe and the corrosion test device at 10m, 100m, 300m, 500m, 800m, 1000m and 1200m downhole. The device is equipped with three materials commonly used in oil fields, namely J55, N80 and P110;

[0155] Step 3: Start the steam composite thermal fluid injection process, start to inject steam and composite thermal fluid, the composite thermal fluid is continuously injected from the insulated oil pipe, and the designed amount of composite thermal fluid is injected according to the requirements of the reservoir;

[0156] During the process of injecting the composite thermal fluid, a corrosion inhibitor solution with a concentration of 1000 ppm is continuously injected from the insulated oil pipe;

[0157] Step 4: stew the well;

[0158] Step 5: Spray;

[0159] Step 6: Pull out the underground heat-insulated oil pipe and the corrosion testing device, and take out the corrosion coupon;

[0160] Step 7: Arrange the data: Arrange the weight loss of the corrosion coupons at different downhole depths, calculate the corrosion rate, and then you can get the corrosion rate of continuous injection of corrosion inhibitor at different downhole depths. Fig.11 .

[0161] from Fig.11 It can be seen that: with the increase of the depth of the well, the effect of the corrosion inhibitor gradually worsens. Within the range of 1200 meters of the well depth, the corrosion rates of N80 steel and P110 steel after treatment with corrosion inhibitor are lower than 0.076mm / a, which meets the on-site requirements.

[0162] Embodiment 8:

[0163] A test method for evaluating the performance of a corrosion inhibitor at different temperatures of a composite thermal fluid comprises the following steps:

[0164] Step 1: Pull out the production string from the original well;

[0165] Step 2: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device. At 800m downhole, lower the insulation oil pipe and the corrosion test device at the same time. The device is equipped with three materials commonly used in oil fields, namely new J55, N80 and P110.

[0166] Step 3: Start the steam composite thermal fluid injection process, start to inject steam and composite thermal fluid, the composite thermal fluid is continuously injected from the insulated oil pipe, and the designed amount of composite thermal fluid is injected according to the requirements of the reservoir;

[0167] The wellhead injection temperature of the composite thermal fluid is 350°C;

[0168] During the process of injecting the composite thermal fluid, a corrosion inhibitor solution with a concentration of 1000 ppm is continuously injected from the insulated oil pipe;

[0169] Step 4: stew the well;

[0170] Step 5: Spray;

[0171] Step 6: Pull out the underground insulation oil pipe and the corrosion test device, take out the corrosion coupon, and calculate the corrosion rate of the corrosion inhibitor when the injection temperature is 350°C;

[0172] Step 7, repeating steps 1 to 6, wherein the injection temperature of the composite thermal fluid in step 3 is 300° C., and calculating the corrosion rate of the corrosion inhibitor when the injection temperature is 300° C.;

[0173] Step 8, repeating steps 1 to 6, wherein the injection temperature of the composite thermal fluid in step 3 is 280° C., and calculating the corrosion rate of the corrosion inhibitor when the injection temperature is 280° C.;

[0174] Step 9, repeating steps 1 to 6, wherein the injection temperature of the composite thermal fluid in step 3 is 250° C., and calculating the corrosion rate of the corrosion inhibitor when the injection temperature is 250° C.;

[0175] Step 10, sorting data: sort out the weight loss mass of the corrosion inhibitor injected continuously at different composite thermal fluid temperatures, calculate the corrosion rate, and obtain the corrosion rate of the corrosion inhibitor injected continuously at different composite thermal fluid temperatures, and evaluate the temperature resistance of the corrosion inhibitor, see Table 1;

[0176] Table 1 Performance evaluation of corrosion inhibitors at different temperatures of composite thermal fluid

[0177]

[0178] It can be seen from Table 1 that with the increase of the injection temperature of the composite thermal fluid, the effect of the corrosion inhibitor gradually worsens. Within the temperature range of 350°C of the composite thermal fluid, the corrosion rates of N80 steel and P110 steel after corrosion inhibitor treatment are both lower than 0.076 mm / a, meeting the site requirements.

[0179] Embodiment 9:

[0180] A test method for evaluating the performance of corrosion inhibitors with different oxygen contents in a composite thermal fluid comprises the following steps:

[0181] Step 1: Pull out the production string from the original well;

[0182] Step 2: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device. At 800m downhole, lower the insulation oil pipe and the corrosion test device at the same time. The device is equipped with three materials commonly used in oil fields, namely new J55, N80 and P110.

[0183] Step 3: Start the steam composite thermal fluid injection process, start to inject steam and composite thermal fluid, the composite thermal fluid is continuously injected from the insulated oil pipe, and the designed amount of composite thermal fluid is injected according to the requirements of the reservoir;

[0184] The oxygen content in the composite thermal fluid is 5%;

[0185] During the process of injecting the composite thermal fluid, a corrosion inhibitor solution with a concentration of 1000 ppm is continuously injected from the insulated oil pipe;

[0186] Step 4: stew the well;

[0187] Step 5: Spray;

[0188] Step 6: Pull out the underground insulated oil pipe and the corrosion test device, take out the corrosion coupon, and calculate the corrosion rate of the continuous injection of the corrosion inhibitor when the oxygen concentration is 5%;

[0189] Step 7: Repeat steps 1 to 6. In step 3, the oxygen content in the composite thermal fluid is 3%. Calculate the corrosion rate of the corrosion inhibitor when the oxygen concentration is 3%.

[0190] Step 8: Repeat steps 1 to 6. In step 3, the oxygen content in the composite thermal fluid is 1%. Calculate the corrosion rate of the corrosion inhibitor when the oxygen concentration is 1%.

[0191] Step 9, repeating steps 1 to 6, wherein the oxygen content in the composite thermal fluid in step 3 is 0.5%, and calculating the corrosion rate of the corrosion inhibitor when the oxygen concentration is 0.5%;

[0192] Step 10, data collation: collate the weight loss of the coupons with different oxygen contents, calculate the corrosion rate, and obtain the corrosion rate of the corrosion inhibitor when the oxygen content is continuously injected, so as to evaluate the slow release performance of the corrosion inhibitor on the oxygen in the corrosive medium, see Table 2;

[0193] Table 2 Evaluation table of corrosion inhibitor performance with different oxygen contents in composite thermal fluid

[0194]

[0195] It can be seen from Table 2 that with the increase of oxygen concentration, the effect of corrosion inhibitor gradually worsens. Within the temperature range of oxygen concentration within 5%, the corrosion rates of N80 steel and P110 steel after corrosion inhibitor treatment are both lower than 0.076 mm / a, which meets the site requirements.

[0196] Embodiment 10:

[0197] A test method for evaluating the performance of a corrosion inhibitor with different carbon dioxide contents in a composite thermal fluid comprises the following steps:

[0198] Step 1: Pull out the production string from the original well;

[0199] Step 2: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device. At 800m downhole, lower the insulation oil pipe and the corrosion test device at the same time. The device is equipped with three materials commonly used in oil fields, namely new J55, N80 and P110.

[0200] Step 3: Start the steam composite thermal fluid injection process, start to inject steam and composite thermal fluid, the composite thermal fluid is continuously injected from the insulated oil pipe, and the designed amount of composite thermal fluid is injected according to the requirements of the reservoir;

[0201] The content of carbon dioxide in the composite thermal fluid is 25%;

[0202] During the process of injecting the composite thermal fluid, a corrosion inhibitor solution with a concentration of 1000 ppm is continuously injected from the insulated oil pipe;

[0203] Step 4: stew the well;

[0204] Step 5: Spray;

[0205] Step 6: Pull out the underground insulated oil pipe and the corrosion test device, take out the corrosion coupon, and calculate the corrosion rate of the continuous injection of the corrosion inhibitor when the carbon dioxide content is 25%;

[0206] Step 7, repeating steps 1 to 6, wherein the content of carbon dioxide in the composite thermal fluid in step 3 is 20%, and calculating the corrosion rate of the continuous injection of the corrosion inhibitor when the carbon dioxide content is 20%;

[0207] Step 8, repeating steps 1 to 6, wherein the content of carbon dioxide in the composite thermal fluid in step 3 is 15%, and calculating the corrosion rate of the continuous injection of the corrosion inhibitor when the carbon dioxide content is 15%;

[0208] Step 9, repeating steps 1 to 6, wherein the content of carbon dioxide in the composite thermal fluid in step 3 is 10%, and calculating the corrosion rate of the corrosion inhibitor when the content of carbon dioxide is 10%;

[0209] Step 10, data collation: collate the weight loss of the coupons with different carbon dioxide contents, calculate the corrosion rate, and obtain the corrosion rate of the corrosion inhibitor when the carbon dioxide content is continuously injected, so as to evaluate the slow release performance of the corrosion inhibitor to the corrosive medium carbon dioxide, see Table 3;

[0210] Table 3 Evaluation table of corrosion inhibitor performance at different carbon dioxide contents in composite thermal fluid

[0211]

[0212] It can be seen from Table 3 that with the increase of carbon dioxide concentration, the effect of the corrosion inhibitor gradually worsens. Within the temperature range of carbon dioxide concentration within 20%, the corrosion rates of N80 steel and P110 steel after corrosion inhibitor treatment are both lower than 0.076 mm / a, meeting the site requirements.

[0213] Embodiment 11:

[0214] A test method for evaluating the corrosion inhibition performance of a composite thermal fluid when different corrosion inhibitor concentrations are added thereto comprises the following steps:

[0215] Step 1: Pull out the production string from the original well;

[0216] Step 2: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device. At 800m downhole, lower the insulation oil pipe and the corrosion test device at the same time. The device is equipped with three materials commonly used in oil fields, namely new J55, N80 and P110.

[0217] Step 3: Start the steam composite thermal fluid injection process, start to inject steam and composite thermal fluid, the composite thermal fluid is continuously injected from the insulated oil pipe, and the designed amount of composite thermal fluid is injected according to the requirements of the reservoir;

[0218] During the process of injecting the composite thermal fluid, a corrosion inhibitor solution with a concentration of 1000 ppm is continuously injected from the insulated oil pipe;

[0219] Step 4: stew the well;

[0220] Step 5: Spray;

[0221] Step 6: Pull out the underground insulated oil pipe and the corrosion test device, take out the corrosion coupon, and calculate the corrosion rate when the corrosion inhibitor concentration is 1000ppm;

[0222] Step 7, repeating steps 1 to 6, wherein the concentration of the corrosion inhibitor continuously injected in step 3 is 800 ppm, and calculating the corrosion rate when the corrosion inhibitor concentration is 800 ppm;

[0223] Step 8, repeating steps 1 to 6, wherein the concentration of the corrosion inhibitor continuously injected in step 3 is 1200 ppm, and calculating the corrosion rate when the corrosion inhibitor concentration is 1200 ppm;

[0224] Step 9, repeating steps 1 to 6, wherein the concentration of the corrosion inhibitor continuously injected in step 3 is 1500 ppm, and calculating the corrosion rate when the corrosion inhibitor concentration is 1500 ppm;

[0225] Step 10, sorting data: sorting out the weight loss of the coupons when different corrosion inhibitor concentrations are continuously injected, calculating the corrosion rate, and obtaining the corrosion inhibition effect when different corrosion inhibitor concentrations are added to the composite thermal fluid, so as to optimize the concentration of the corrosion inhibitor, see Table 4;

[0226] Table 4 Corrosion inhibition performance evaluation table when different corrosion inhibitor concentrations are added to the composite thermal fluid

[0227]

[0228] It can be seen from Table 4 that as the concentration of the corrosion inhibitor increases, the slow-release effect of the corrosion inhibitor becomes better. The optimal concentration of the corrosion inhibitor is preferably 1000 ppm. The corrosion rates of N80 steel and P110 steel after treatment with the corrosion inhibitor are both lower than 0.076 mm / a, which meets the on-site requirements.

[0229] Embodiment 12:

[0230] A test method for evaluating the corrosion inhibition performance of a corrosion inhibitor in a composite thermal fluid under different injection modes comprises the following steps:

[0231] Step 1: Pull out the production string from the original well;

[0232] Step 2: Lower the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion test device. At 800m downhole, lower the insulation oil pipe and the corrosion test device at the same time. The device is equipped with three materials commonly used in oil fields, namely new J55, N80 and P110.

[0233] Step 3: inject a corrosion inhibitor solution with a concentration of 1000ppm from the insulated oil pipe and soak for 2 to 3 days to perform a corrosion inhibitor soaking pre-filming treatment on the corrosion coupon;

[0234] Step 4: Start the steam composite thermal fluid injection process, start injecting steam and composite thermal fluid, the composite thermal fluid is continuously injected from the insulated oil pipe, and the designed amount of composite thermal fluid is injected according to the requirements of the oil reservoir;

[0235] Step 5: Stewing the well;

[0236] Step 6: Spray;

[0237] Step 7: Pull out the underground insulated oil pipe and the corrosion test device, take out the corrosion coupons, and calculate the slow-release effect of the corrosion inhibitor soaking pre-filming treatment;

[0238] Step 8. Repeat steps 1 to 7;

[0239] In step 3, a corrosion inhibitor solution with a concentration of 1000 ppm is injected from the insulated oil pipe and immersed for 2 to 3 days to perform a pre-filming treatment of the corrosion coupons with the corrosion inhibitor;

[0240] In the step 4, a corrosion inhibitor solution with a concentration of 1000 ppm is injected from the insulation oil pipe segment plug;

[0241] Step 9, sorting data: sorting out the weight loss of the coupons in three cases of pre-filming treatment, pre-filming treatment + slug injection and continuous injection under the condition of injecting the same amount of corrosion inhibitor, calculating the corrosion rate, and obtaining the corrosion inhibition effect of different injection methods of corrosion inhibitor in the composite thermal fluid, so as to optimize the injection method of corrosion inhibitor, see Table 5;

[0242] Table 5 Evaluation of corrosion inhibition performance of corrosion inhibitors in composite thermal fluids under different injection methods

[0243]

[0244]

[0245] It can be seen from Table 5 that when the same amount of corrosion inhibitor is injected, the corrosion inhibitor injection method of pre-filming treatment + slug injection is the best. The corrosion rate of N80 steel is 0.07 mm / a, and the release rate is 87%; the corrosion rate of N80 steel is 0.067 mm / a, and the release rate is 86%, both of which can meet the on-site requirements.

[0246] Any feature disclosed in this specification (including any additional claims, abstract and drawings), unless otherwise stated, may be replaced by other equivalent or alternative features with similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.

[0247] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. Composite thermal fluid downhole corrosion testing device, characterized in that: The composite thermal fluid downhole corrosion testing device includes a thermal insulation sleeve, a test piece retaining ring, a test piece base and a test piece fixing ring. The thermal insulation sleeve includes a sleeve and a steel liner. The sleeve is sleeved on the outer middle position of the steel liner. The test piece retaining ring is welded to the inner bottom end of the steel liner. The test piece base is clamped on the upper part of the test piece retaining ring. Three test piece grooves are provided on the test piece base. Test pieces of three different materials are respectively placed in the three test piece grooves. The three test pieces are fixed at the upper end of the steel liner by the test piece fixing ring. The composite thermal fluid downhole corrosion testing device is installed in a coupling between two adjacent steam injection pipe columns.

2. The composite thermal fluid downhole corrosion testing device according to claim 1, characterized in that: The test piece retaining ring and the steel liner are made of steel material, and the bushing, the test piece base and the test piece fixing ring are made of high temperature resistant and corrosion resistant sealing insulating materials.

3. The composite thermal fluid downhole corrosion testing device according to claim 1, characterized in that: The three test piece grooves are spaced 120 degrees apart.

4. The composite thermal fluid downhole corrosion testing device according to claim 3, characterized in that: The test piece fixing ring is provided with three rectangular fixing holes with the same cross-sectional area as the test piece and spaced 120 degrees apart.

5. Composite thermal fluid downhole corrosion testing method, characterized in that: The composite thermal fluid downhole corrosion testing method adopts the composite thermal fluid downhole corrosion testing device according to claim 1, comprising: Step 1: Pull out the original well production string; Step 2, lowering the steam injection insulation oil pipe and the composite thermal fluid downhole corrosion testing device; Step 3, starting the steam composite thermal fluid injection process; Step 4, stewing well; Step 5, spray; Step 6: Pull out the underground heat-insulated oil pipe and the corrosion testing device, and take out the corrosion coupon; Step 7: After the corrosion coupon is decontaminated, it is further degreased and dehydrated to obtain the weight loss of the coupon and calculate the corrosion rate.

6. The composite thermal fluid downhole corrosion testing method according to claim 5, characterized in that: In step 2, while lowering the insulated oil pipe, the corrosion testing device is also lowered; the steam injection insulated oil pipe is a high vacuum or aerogel insulated oil pipe.

7. The composite thermal fluid downhole corrosion testing method according to claim 5, characterized in that: In step 3, steam and composite thermal fluid are injected, and the composite thermal fluid is continuously injected from the insulated oil pipe, and the designed amount of composite thermal fluid is injected according to the requirements of the reservoir.

8. The composite thermal fluid downhole corrosion testing method according to claim 5, characterized in that: In step 4, after the injection of the composite thermal fluid is completed, a temperature-resistant pressure gauge is installed at the wellhead and the well is shut down. The shut down time depends on the injection volume of the composite thermal fluid and the wellhead pressure, and should be adjusted according to actual conditions.

9. The composite thermal fluid downhole corrosion testing method according to claim 5, characterized in that: In step 5, the spraying is controlled by an oil nozzle to prevent the formation from being disturbed and the sand filter pipe from being eroded due to excessive spraying speed. When the liquid volume reaches 3t / d, the pumping is switched to suction.

10. The composite thermal fluid downhole corrosion testing method according to claim 5, characterized in that: The composite thermal fluid downhole corrosion testing method further includes, after step 6, observing and recording the surface corrosion state and corrosion product adhesion of the hanging piece, cleaning it with clean water, and wiping it dry with filter paper.

11. The composite thermal fluid downhole corrosion testing method according to claim 5, characterized in that: In step 7, the corrosion coupon is placed in a container of petroleum ether or acetone, and the oil on the surface of the corrosion coupon is removed with absorbent cotton, and then immersed in sewage ethanol for 5 minutes for further degreasing and dehydration; then the corrosion coupon is placed in the prepared pickling solution and immersed for 5 minutes, and at the same time, a small amount of absorbent cotton is clamped with tweezers to gently wipe the corrosion products on the surface of the coupon; the coupon is taken out from the cleaning solution, and the residual acid on the surface is washed off with tap water, and then the coupon is immediately immersed in a sodium hydroxide solution, rinsed with tap water after 30 seconds, and then immersed in anhydrous ethanol for 5 minutes, and washed and dehydrated twice; the coupon is taken out and placed on filter paper, blown dry with cold wind, and then wrapped with filter paper, placed in a dryer, and weighed after 24 hours to obtain the weight loss of the coupon, and the corrosion rate is calculated.

12. The composite thermal fluid downhole corrosion testing method according to claim 11, characterized in that: In step 7, the corrosion rate is calculated as: Where: r c represents the average corrosion rate in millimeters per year; m represents the mass of the test piece before the test in grams; m1 represents the mass of the test piece after the test in grams; S represents the total area of ​​the test piece in square centimeters; t represents the test time in hours; ρ represents the density of the test piece material in grams per cubic centimeter.

13. The composite thermal fluid downhole corrosion testing method according to claim 5, characterized in that: The composite thermal fluid downhole corrosion testing method also includes, after step 7, repeating steps 1 to 6, during the injection of the composite thermal fluid in step 3, the pump truck is connected to the oil pipe gate through a hose, and the corrosion inhibitor solution is continuously or segmentally injected, and the corrosion inhibition efficiency of the corrosion inhibitor under different field conditions is evaluated by the weight loss method.

Citation Information

Patent Citations

  • High-temperature high-pressure constant load stress corrosion experiment method and device

    CN102706750B

  • Experimental apparatus for simulating stress corrosion of metal material under actual working conditions

    CN105021455A

  • Downhole stress corrosion testing method and device

    CN105973793A

  • A method for evaluating the corrosion inhibition efficiency of corrosion inhibitors

    CN106841026B

  • A corrosion inhibitor evaluation integrated device and use method thereof

    CN109724911B